The Relationship between the Quality of Health Services and The Satisfaction of Families’ Patients at Intensive Care Unit - Amalia, Endra; Sefrila, Sefrila; Delima, Mera; Suri, Marta (REAL in Nursing Journal, 2025)
Quality service health is determinant main satisfaction family patients, especially in intensive care units intensive (Sutoyo and Rusdi, 2023) . Survey Index Public Satisfaction of Sungai Dareh Regional General Hospital 2023 shows score 76.02, decreased from 76.77 in 2020 and not yet reach minimum standard ≥ 90%. Dominant complaints covering delay service, lack of information clear medical, as well as cleanliness facilities are not optimal. Research This aim For analyze connection between quality service health and satisfaction family patients in the Intensive Care Unit of Sungai Dareh Hospital. Research use design analytic correlational with cross-sectional approach and involved 44 selected respondents by accidental sampling. Data collected through questionnaire and analyzed using the Chi-Square test. The results showed that 86.4% of respondents evaluate service good, and 65.8% of them feel satisfied. On the other hand, 83.3% of respondents who assessed service not enough Good feel No satisfied. Statistical test show connection significant between quality service and satisfaction family patients (p = 0.034). These results confirm importance improvement quality services, especially in aspect communication, accuracy time, cleanliness, and responsiveness power health For increase satisfaction users service.